2008
DOI: 10.1038/nature07391
|View full text |Cite
|
Sign up to set email alerts
|

Sox18 induces development of the lymphatic vasculature in mice

Abstract: The lymphatic system plays a key role in tissue fluid regulation and tumour metastasis, and lymphatic defects underlie many pathological states including lymphoedema, lymphangiectasia, lymphangioma and lymphatic dysplasia. However, the origins of the lymphatic system in the embryo, and the mechanisms that direct growth of the network of lymphatic vessels, remain unclear. Lymphatic vessels are thought to arise from endothelial precursor cells budding from the cardinal vein under the influence of the lymphatic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
521
2
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 497 publications
(555 citation statements)
references
References 32 publications
11
521
2
11
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27][28][29][30] In fact, few studies have revealed the significance of SOX group F gene expression in human cancer, although cell line-based studies have demonstrated that both SOX 18 and SOX 7 were highly expressed in several strains of gastric, pancreatic and esophageal cancer cell lines. 22,32 In the present study, SOX group F gene expression determined by RT-PCT was increased in gastric cancer tissues than in normal gastric tissues obtained from the same individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25][26][27][28][29][30] In fact, few studies have revealed the significance of SOX group F gene expression in human cancer, although cell line-based studies have demonstrated that both SOX 18 and SOX 7 were highly expressed in several strains of gastric, pancreatic and esophageal cancer cell lines. 22,32 In the present study, SOX group F gene expression determined by RT-PCT was increased in gastric cancer tissues than in normal gastric tissues obtained from the same individuals.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Thus, interfering with SOX 18 function, both blood vessel formation and subsequent tumor growth are inhibited and this process is responsible for the lymphatic defect in hypotrichosis-lymphoedema-telangiectasia. [25][26][27][28] The SOX 7 and SOX 17 genes are also known to have compensatory roles during angiogenesis and lymphangiogenesis. [19][20][21] It has been demonstrated that blood circulation in SOX 7 and SOX 18 double knock-down zebrafish was blocked in the trunk and tail due to multiple fusions between the axial vessels.…”
mentioning
confidence: 99%
“…SRY-related HMG-box 18 (Sox18), a member of the F-group of Sox transcription factors, has been identified to bind upstream of PROX1 and up-regulate Prox1 expression (François et al 2008). Moreover, mice carrying a natural Sox18-dominant-negative mutation fail to initiate Prox1 up-regulation in venous endothelial cells during development and to develop a normal lymphatic system (François et al 2008).…”
Section: Prox1: the Master Regulator For Lymphatic Developmentmentioning
confidence: 99%
“…SRY-related HMG-box 18 (Sox18), a member of the F-group of Sox transcription factors, has been identified to bind upstream of PROX1 and up-regulate Prox1 expression (François et al 2008). Moreover, mice carrying a natural Sox18-dominant-negative mutation fail to initiate Prox1 up-regulation in venous endothelial cells during development and to develop a normal lymphatic system (François et al 2008). Importantly, humans with mutations in Sox18 develop a blood/lymphatic vascular disease, hypotrichosis-lymphedematelangiectasia (HLT), which is characterized by alopecia, hemorrhage, and lymphedema (Irrthum et al 2003).…”
Section: Prox1: the Master Regulator For Lymphatic Developmentmentioning
confidence: 99%
“…1C, Ra Op/+ ). The Ra Op mutant mice carry a natural mutation in the Sox18 [SRY (sex determining region Y) box 18] gene (11,12) that triggers the production of a truncated nonfunctional protein that suppresses F-group SOX (Sox7, Sox17, and Sox18) proteins in blood vessels. During lymphangiogenesis, Sox18 is expressed in venous cells to induce Prox-1 expression (11); at the same embryonic stages, Foxc1 and Foxc2 are required to maintain artery vs. vein specification (13).…”
mentioning
confidence: 99%